Philosophy and Social Sciences toward the Bicentennial - Elgregren Reátegui, Fernando (2017)
This paper examines different approaches of social scientists and philosophers in the face of the national reality of Peru, specifically with respect to State-society relations and the Peruvian citizen in general. It considers the hypothesis that the State and Philosophy in Peru have hindered the formation of citizenship, contributing to this the lack of interdisciplinarity studies between philosophy and the social sciences. The article is the result of some initial reflections that, from the Department of Philosophy and Theology at UNIFÉ, seek to create awareness of the challenges that we need to face towards the Bicentennial.